Time to thrombectomy is associated with increased risk for dialysis catheter placement. Issue 4 (26th August 2019) - Hall, Damian; Shaughnessy, Daniel; Drawz, Paul; Akkina, Sunil; Esten, Andrew; Foley, Robert N.; Reule, Scott
SUMMARY: Background: Arteriovenous dialysis access, fistulae (AVF) or grafts (AVG), are associated with significant rates of thrombosis. Timely thrombectomy may have a significant impact on immediate and long‐term access survival. However, switching to a catheter is associated with higher rates of morbidity and mortality compared with those who have an AVF or AVG. Objectives: The goal of this study was to evaluate whether time to thrombectomy increases the risk for loss of dialysis access and subsequent placement of a dialysis catheter at hospital discharge, at 6 months, 12 months, and data at any time after discharge. Methods: Using retrospective data, 444 patients were identified as having undergone thrombectomy for dialysis access dysfunction between January 2008 and April 2015, with 122 hospital admissions primarily for thrombectomy. Results: The mean age was 60.4 years, 65% were male, and 44.3% had an arteriovenous fistula as their dialysis access. The mean time to thrombectomy was 10.8 hours, and 14 patients utilised a catheter for haemodialysis as primary access upon discharge. After adjustment for prior access intervention, access type, and time to thrombectomy, the adjusted odds ratios (AOR) of a one‐day delay in thrombectomy was associated with a twofold increase in requirement for catheter at discharge and at 6 months. This association remained present at any time after discharge. Conclusion: In this study of patients cared for within an academic health system, a single day delay in thrombectomy nearly doubled the risk of needing a dialysis catheter at hospital discharge, 6 months, or any time after discharge.